Witchcraft, Envy, and Norm Enforcement in Mauritius - Willard, Aiyana K; Rosun, Nachita; Lesage, Kirsten; Horský, Jan; Xygalatas, Dimitris (Human nature (Hawthorne, N.Y.), 2024)
Recent research has shown that an array of religious beliefs can be used to enforce socially normative behaviour, but the application of these theories to other supernatural beliefs, including witchcraft, is still nascent. Across two pre-registered studies in Mauritius, we examine how witchcraft is believed to be caused by envy and how this belief can create and enforce social norms around not causing envy. Data was collected in-person in Mauritius. In study 1 (N = 445), we found that both practicing witchcraft and being motivated by envy or self-interest increase perceptions of harm. These motivations also increase the rate with which people suggest a person was doing witchcraft, with envy having the stronger effect. Belief that someone was doing witchcraft increases the negativity with which one views that person and damages their reputation. In study 2 (N = 292), we found that when a person breaks a norm around causing envy, participants believe that a subsequent misfortune is cause by witchcraft, but not by God. When someone acts selfishly towards others a subsequent misfortune is believed to be caused by God but not witchcraft. This suggests that witchcraft beliefs, but not religious ones, are enforcing norms around preventing envy. Together, these studies suggest that witchcraft beliefs can support locally specific social norms, and that these norms might be different than those supported by religion.
Keywords: Mauritius; čarodějnictví; Norm enforcement; Social Norms; mladiství; Middle Aged; mužské pohlaví; Mauricius; Religion; Adult; mladý dospělý; Supernatural punishment; sociální normy; náboženství a psychologie; Young Adult; ženské pohlaví; Witchcraft; Humans; žárlivost; lidé středního věku; Supernatural retribution; Envy; dospělí; Female; Religion and Psychology; Adolescent; Jealousy; lidé; Male